Tribology of Machine Elements - Fundamentals and Applications 2022
DOI: 10.5772/intechopen.100245
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Performance of Random Sinter Pores vs. Deterministic Laser Surface Textures: An Experimental and Machine Learning Approach

Abstract: This work critically scrutinizes and compares the tribological performance of randomly distributed surface pores in sintered materials and precisely tailored laser textures produced by different laser surface texturing techniques. The pore distributions and dimensions were modified by changing the sintering parameters, while the topological features of the laser textures were varied by changing the laser sources and structuring parameters. Ball-on-disc tribological experiments were carried out under lubricated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…It is important to note that the textures resulting from machining of the tools are stochastic, meaning they display randomness in dimensions, distribution, or organization. However, Boidi et al [21] showed that stochastic textures offer tribological performance similar to deterministic textures with precisely defined distributions and arrangements.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to note that the textures resulting from machining of the tools are stochastic, meaning they display randomness in dimensions, distribution, or organization. However, Boidi et al [21] showed that stochastic textures offer tribological performance similar to deterministic textures with precisely defined distributions and arrangements.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, there is a number of review articles showcasing the usages and many promises of AI and ML within tribology [1,2,[28][29][30][31]. However, a challenge remains in the training of AI/ML models, which relies heavily on the availability of large amounts of high-quality experimentally [32][33][34][35][36][37][38] or numerically [39][40][41][42] generated data. Ideally, these data should be FAIR (Findable, Accessible, Interoperable, and Reusable), meaning it should be well documented, easily accessible, compatible with different systems, and suitable for reuse in different contexts [43][44][45].…”
Section: Artificial Intelligence and Machine Learning In Tribologymentioning
confidence: 99%
“…Generally, textures were able to reduce friction especially at low sliding speeds and a small texture radius with a rather high area density was reported to be most beneficial. Boidi et al [139,355] employed a Hardy multiquadric radial base function to predict the wear behaviour of sintered components under varying operating conditions in a ball-on-disk setup (mini-traction machine and lubricant film thickness measurements based on optical interferometry) as well as geometric or statistical characteristics of the dimples, grooves, and pores.…”
Section: Hard Ehl Contactsmentioning
confidence: 99%